Depression among Chronic Kidney Diseases Patients Receiving Hemodialysis - Khadka, Shanti; Adhikari, Rita; Paudel, Tarun (Journal of Karnali Academy of Health Sciences, 2020)
Background: Chronic Kidney Disease (CKD) is a progressive irreversible loss of renal function over a period of months or years. When kidney disease progresses, it may eventually lead to kidney failure, which requires dialysis or a kidney transplant to maintains life. Hemodialysis is used for patients who require short term dialysis (days to weeks) and for patients with advanced CKD and End Stage renal Disease (ESRD) who require long term or permanent renal replacement therapy. Hemodialysis significantly and adversely affects the lives of patients, both physically and psychologically. Depression is the most common psychological condition among patients with ESRD. Depression in dialysis patients not only effect mortality, but increased rate of hospitalizations and dialysis withdrawal is also very common.Methods: A descriptive cross sectional research design was carried out to identify the depression level of chronic kidney disease patients receiving Hemodialysis in Western Regional Hospital, Pokhara using Beck Depression Inventory among forty six patients.Results: The study findings revealed that majority of the patients (84.8%) has various degree of depression i.e. mild (21.7%), moderate (30.8%) and severe (32.6%). Only fifteen percent of patient has no depression. There was no statistical association between the level of depression and socio-demographic variables. It can be concluded that the prevalence of depression is high among patients receiving Hemodialysis.Conclusion: The prevalence of depression is high among patients receiving Hemodialysis. It is effective to provide mental health services to the CKD patients receiving Hemodialysis which help them better psychologically adaptation to their disease and improve their quality of life.